Health disparities in aging: Improving dementia care for Black women - Findley, Caleigh A.; Cox, MaKayla F.; Lipson, Adam B.; Bradley, RaTasha; Hascup, Kevin N.; Yuede, Carla; Hascup, Erin R. (Frontiers in Aging Neuroscience, 2023)
In the United States, 80% of surveyed Black patients report experiencing barriers to healthcare for Alzheimer’s disease and related dementias (ADRD), delaying the time-sensitive treatment of a progressive neurodegenerative disease. According to the National Institute on Aging, Black study participants are 35% less likely to be given a diagnosis of ADRD than white participants, despite being twice as likely to suffer from ADRD than their white counterparts. Prior analysis of prevalence for sex, race, and ethnicity by the Centers for Disease Control indicated the highest incidence of ADRD in Black women. Older (≥65 years) Black women are at a disproportionately high risk for ADRD and yet these patients experience distinct inequities in obtaining clinical diagnosis and treatment for their condition. To that end, this perspective article will review a current understanding of biological and epidemiological factors that underlie the increased risk for ADRD in Black women. We will discuss the specific barriers Black women face in obtaining access to ADRD care, including healthcare prejudice, socioeconomic status, and other societal factors. This perspective also aims to evaluate the performance of intervention programs targeted toward this patient population and offer possible solutions to promote health equity.